2015
DOI: 10.1111/iju.12715
|View full text |Cite
|
Sign up to set email alerts
|

p21‐activated kinase 1 predicts recurrence and survival in patients with non‐metastatic clear cell renal cell carcinoma

Abstract: Objectives: To estimate the impact of p21-activated kinase 1 expression on recurrence and survival of patients with non-metastatic clear cell renal cell carcinoma after surgical resection. Methods: We retrospectively enrolled 254 patients (187 in the training cohort and 67 in the validation cohort) with non-metastatic clear cell renal cell carcinoma undergoing nephrectomy at a single institution. Clinicopathological features, overall survival and recurrence-free survival were recorded. p21-activated kinase 1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Although several pathologic parameters, including lymphatic vessel invasion [45], tumor fat invasion [26] and primary tumor size [43], provide independent prognostic information, the likely outcome for an individual patient remains uncertain. The TNM stage and Fuhrman grade system are the most widely used approaches for RCC; however, there have been many recent suggestions for modifications based on survival trends in large case series [46]. Additionally, RCC is a highly heterogeneous disease with different clinical presentations and characteristics that remain somewhat unpredictable [47].…”
Section: Discussionmentioning
confidence: 99%
“…Although several pathologic parameters, including lymphatic vessel invasion [45], tumor fat invasion [26] and primary tumor size [43], provide independent prognostic information, the likely outcome for an individual patient remains uncertain. The TNM stage and Fuhrman grade system are the most widely used approaches for RCC; however, there have been many recent suggestions for modifications based on survival trends in large case series [46]. Additionally, RCC is a highly heterogeneous disease with different clinical presentations and characteristics that remain somewhat unpredictable [47].…”
Section: Discussionmentioning
confidence: 99%
“…PAK1 is over-expressed in various malignancies such as ovarian, breast, lung, and bladder cancers, and is closely associated with tumor invasion20, 21. The PAK1 expression level is positively correlated with tumor progression, metastases, and poor prognosis of specific carcinomas20, 22, 23. The inhibition of PAK1 expression or disruption of its function may significantly inhibit cancer cell proliferation and metastasis18, 19, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the International Journal of Urology , Zhu et al . reported the results of a single institutional retrospective study of East Asian patients with localized clear cell RCC that was designed to determine the outcomes of patients with this disease and the prognostic factors . Zhu et al .…”
mentioning
confidence: 99%
“…examined p21‐activated kinase 1 (PAK1), which is a serine/threonine kinase that orchestrates cytoskeletal remodeling and cell motility. PAK1 has been shown to play various oncogenic roles in promoting cell proliferation, regulating apoptosis and accelerating mitotic abnormalities, all of which result in tumor formation and invasiveness . They showed that high PAK1 expression indicated poor survival and early disease recurrence in patients with non‐metastatic clear cell RCC, particularly those with early T1–2 stage disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation